Analysis of Arabic Teaching Modules in the Independent Curriculum at Madrasah Tarbiyah Islamiyah Pasia Agam: تحليل المواد التّعليمية للغة العربيّة في منهج مرديكا بمدرسة التّربيّة الإسلاميّة باسر أغام - Putri, Rahma; Eka Rizal; Yelfi Dewi; Fajriyani Arsya (Ukazh : Journal of Arabic Studies, 2025)
In the context of the Merdeka Curriculum, teaching modules serve as one of the main instruments designed to assist teachers in implementing student-centered learning by taking into account the characteristics, needs, and potential of each learner. This condition poses  a challenge for teachers to design and develop teaching modules properly so that the learning process becomes effective. This study aims to identify the componensts of the teaching modules used by the teachers and to analyze whether the grade VII Arabic language teaching modules developed by teachers at Madrasah Tarbiyah Islamiyah Pasia are in accordance with the guidelines issued by the ministry of religious affairs. The research method used is descriptive qualitative with data collection techniques through documentation and interviews. The results of this study indicate that the Arabic teaching module created by the teacher consists of general informationm, learning objectives, learning steps, media, and assessments used, and already includes the minimum components stated in the guideline. However, in general, the Arabic teaching module used has not fully complied with the structure and guidelines of the ministry of religious affairs in terms of the complete components. Therefore,  this Study recommends the need for intensive training for teachers in developing teaching modules that comply with the provisions of the Merdeka Curriculum.